m6A RNA methylation: from mechanisms to therapeutic potential - He, P Cody; He, Chuan (The EMBO journal, 2021)
RNA carries a diverse array of chemical modifications that play important roles in the regulation of gene expression. N 6 ‐methyladenosine (m 6 A), installed onto mRNA by the METTL3/METTL14 methyltransferase complex, is the most prevalent mRNA modification. m 6 A methylation regulates gene expression by influencing numerous aspects of mRNA metabolism, including pre‐mRNA processing, nuclear export, decay, and translation. The importance of m 6 A methylation as a mode of post‐transcriptional gene expression regulation is evident in the crucial roles m 6 A‐mediated gene regulation plays in numerous physiological and pathophysiological processes. Here, we review current knowledge on the mechanisms by which m 6 A exerts its functions and discuss recent advances that underscore the multifaceted role of m 6 A in the regulation of gene expression. We highlight advances in our understanding of the regulation of m 6 A deposition on mRNA and its context‐dependent effects on mRNA decay and translation, the role of m 6 A methylation of non‐coding chromosomal‐associated RNA species in regulating transcription, and the activities of the RNA demethylase FTO on diverse substrates. We also discuss emerging evidence for the therapeutic potential of targeting m 6 A regulators in disease. Graphical Abstract Roles of the most prevalent RNA modification in post‐transcriptional regulation of gene expression, the latest understanding of its deposition and removal, and the possibility of its targeting in disease are discussed in this comprehensive review.